Addressing the preventive and therapeutic perspective of berberine against diabetes - Suyesh Shrivastava; Anamika Sharma; Nishant Saxena; Rashmi Bhamra; Sandeep Kumar (Heliyon, 2023)
Diabetes has emerged as one the leading detrimental factors for human life expectancy worldwide. The disease is mainly considered as outcome of dysregulation in glucose metabolism, resulting in consistent high glucose concentration in blood. At initial stages, the diabetes particularly type 2 diabetes, is manageable by lifestyle interventions such as regular physical activity and diet with less carbohydrates. However, in advance stage, regular intake of external insulin dose and medicines like metformin are recommended. The long-term consumption of metformin is associated with several side effects such as nausea, vomiting, diarrhoea, lectic acidosis etc., In this scenario, several plant-based medicines have shown promising potential for the prevention and treatment of diabetes. Berberine is the bioactive compound present in the different plant parts of berberis family. Biochemical studies have shown that berberine improve insulin sensitivity and insulin secretion. Additionally, berberine induces glucose metabolism by activating AMPK signaling and inhibition of inflammation. A series of studies have demonstrated the antidiabetic potential of berberine at in vitro, pre-clinical and clinical trials. This review provides comprehensive details of preventive and therapeutic potential of berberine against diabetes.